Inovasi Robot Tong Sampah Otomatis Berbasis Arduino Dengan Reward Dispenser Air Membentuk Karakter Peduli Lingkungan Pada Smp Andalusia - Jatmiko indriyanto; Wilibrordus Megandika Wicaksono (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
Students' awareness of disposing of waste in designated bins remains a challenge in creating a clean and healthy school environment. This study aims to design and develop an Arduino-based automatic smart trash bin equipped with a water dispenser reward system to encourage students to dispose of waste properly. The system uses a sensor to detect waste deposited into the bin, while the Arduino processes the input signal and activates a water pump to dispense drinking water automatically for a predetermined duration. The research employed the Research and Development (R&D) method, including needs analysis, hardware and software design, implementation, testing, and system evaluation. Testing was conducted at SMP Andalusia Kebasen by evaluating the accuracy of waste detection, dispenser response, and user feedback. The results showed that the proposed system operated according to the design with a high success rate in waste detection and dispenser activation. In addition to improving waste disposal practices, the system provided an interactive learning experience that encouraged students to develop greater discipline in maintaining environmental cleanliness. Therefore, the Arduino-based automatic smart trash bin integrated with a reward system has the potential to serve as an effective educational medium for fostering environmental awareness and responsible waste disposal behavior among junior high school students.